Structural Analysis of Fungal Cerebrosides - Barreto-Bergter, Eliana; Sassaki, Guilherme L.; Souza, Lauro (Frontiers in Microbiology, 2011)
Of the ceramide monohexosides (CMHs), gluco- and galactosylceramides are the main neutral glycosphingolipids expressed in fungal cells. Their structural determination is greatly dependent on the use of mass spectrometric techniques, including fast atom bombardment-mass spectrometry (FAB-MS), electrospray ionization (ESI-MS), and energy collision-induced dissociation mass spectrometry (ESI-MS/CID-MS). Nuclear magnetic resonance (NMR) has also been used successfully. Such a combination of techniques, combined with classical analytical separation, such as HPTLC and column chromatography, has led to the structural elucidation of a great number of fungal CMHs. The structure of fungal CMH is conserved among fungal species and consists of a glucose or galactose residue attached to a ceramide moiety containing 9-methyl-4,8-sphingadienine with an amidic linkage to hydroxylated fatty acids, most commonly having 16 or 18 carbon atoms and unsaturation between C-3 and C-4. Along with their unique structural characteristics, fungal CMHs have a peculiar subcellular distribution and striking biological properties. Fungal cerebrosides were also characterized as antigenic molecules directly or indirectly involved in cell growth or differentiation in Schizophyllum commune, Cryptococcus neoformans, Pseudallescheria boydii, Candida albicans, Aspergillus nidulans, A.fumigatus and Colletotrichum gloeosporioides. Besides classical techniques for cerebroside (CMH) analysis, we now describe new approaches, combining conventional TLC and mass spectrometry, as well as emerging technologies for subcellular localization and distribution of glycosphingolipids by SIMS and imaging MALDI TOF .